Land-use, abuse, and institutional attempts for correcting human-nature relationships: Europe vs The Americas - Garrido-Pérez, Edgardo I.; Tella-Ruiz, David; Sidali, Katia Laura; Lincango-Vega, Juan G.; Vélez-Sabando, Luisa M.; Andrade-Alcívar, Luis D. (Ethnobiology and Conservation, 2022)
Warnings regarding pollution, soil-fertility losses, mass extinction, Climate Change, and their effects on humans are widely known since at least 1970, still land-abuse pervasively remains. We aimed to contribute to understand why in order to explore how to reduce land-abuse. We critically compared the history, habitats, and land-uses of the Americas with both Alpine and Lowland Europe focusing on the causes and consequences of land-abuse. We chronologically analyzed the development of the recent European efforts for re-appraising ancestral, more sustainable land-uses (AD 1938-2018). Millionaire profits have fixed a dominant culture of subordination of nature and people to a role of mere commodity-producers in the Americas, making difficult for environmentalism to penetrate into decision-making and institutions. Low-scale, sustainable agriculture remains traditionally practiced by Neotropical and Alpine indigenous peoples, but became increasingly abandoned by lowland Europeans and Americas’ landlords since the first Industrial Revolution. The most effective European efforts for conserving the environment emerged and developed as a sort of interplay with the teaching of Ecology and Conservation in universities that trained prospects of both political activists and decision makers. A result is the preeminently scholarly-made, top-down impulse to sustainable land-use in West Europe. Instead, the most effective environmentalists of the Americas’ are not biologists but grassrooted movements culturally influenced or directly led by indigenous peoples. Nowadays, Europe provides finnancial and economic support to the traditional agriculture of its indigenous farmers. Europe-emulators of the Americas should seek to outbalance land-abuse by supporting and learning from the land-uses of Americas’ indigenous farmers too.